2020
DOI: 10.3390/ijms21249522
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Production of Mitochondrial Reactive Oxygen Species via Hyperthermia Enhanced Cytotoxic Effect of Doxorubicin in Human Breast Cancer Cell Lines MDA-MB-453 and MCF-7

Abstract: Hyperthermia (HT) treatment is a noninvasive cancer therapy, often used with radiation therapy and chemotherapy. Compared with 37 °C, 42 °C is mild heat stress for cells and produces reactive oxygen species (ROS) from mitochondria. To involve subsequent intracellular accumulation of DOX, we have previously reported that the expression of ATP-binding cassette sub-family G member 2 (ABCG2), an exporter of doxorubicin (DOX), was suppressed by a larger amount of intracellular mitochondrial ROS. We then hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Interestingly, co-treatments with 1.56 µg/mL of DOX and HB-AuNPs (HB-AuNPs-DOX) or 1.56 µg/mL of DOX and MGF-AuNPs (MGF-AuNPs-DOX) also induced ROS production; the percentage of cells with high ROS levels was lower for the co-treatments when compared with the treatment with Low DOX alone. The increase in ROS production observed in Caco-2 cells treated with DOX was expected and is in agreement with previous studies [ 41 , 42 ]. The results of this study suggest that the biogenic NPs (HB-AuNPs and MGF-AuNPs) counter or reduce ROS production even in the presence of DOX.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, co-treatments with 1.56 µg/mL of DOX and HB-AuNPs (HB-AuNPs-DOX) or 1.56 µg/mL of DOX and MGF-AuNPs (MGF-AuNPs-DOX) also induced ROS production; the percentage of cells with high ROS levels was lower for the co-treatments when compared with the treatment with Low DOX alone. The increase in ROS production observed in Caco-2 cells treated with DOX was expected and is in agreement with previous studies [ 41 , 42 ]. The results of this study suggest that the biogenic NPs (HB-AuNPs and MGF-AuNPs) counter or reduce ROS production even in the presence of DOX.…”
Section: Resultssupporting
confidence: 93%
“…This can increase blood perfusion, thus facilitating the intratumoral concentration of NPs [ 24 ]. It has been also suggested that modifications to cytoskeletal components may enhance intracellular drug delivery [ 25 ] and promote programmed cell death signaling through the induction of (i) alterations in the cytoskeleton-integrin network [ 26 ] or (ii) reactive oxygen species (ROS) production in mitochondria [ 27 ]. Moreover, nanoparticle-mediated HTT has been reported to increase the apoptosis and necrosis of tumor cells due to collagen fiber damage [ 28 ].…”
Section: Hyperthermia: Properties and Mechanism Of Actionmentioning
confidence: 99%
“…A study with colorectal cancer has demonstrated that hyperthermia increases intracellular DOX concentrations [ 28 ]. In breast cancer, hyperthermia increased intracellular ROS production and downregulated ATP-binding cassette sub-family G member 2 (ABCG2) expression—an exporter of DOX—leading to cell damage enhancement via DOX [ 39 ]. In addition, Blasiak and colleagues demonstrated that DOX-resistant cancer cells exposed first to DOX and then to hyperthermia, needed double the amount of time to completely repair the DNA damaged by DOX, in comparison to their DOX-sensitive counterparts and to normal cells [ 40 ].…”
Section: Introductionmentioning
confidence: 99%